(untitled) (Medico Legal Update, 2020)
A Retrospective study was conducted to assess the prevalence of type 2DM among chronic liver disease in a selected hospital at Kelambakkam, Tamil Nadu. The objectives were to assess the prevalence of type 2DM among patient with chronic liver disease by collecting the data from the medical records of the patients and to find the association between type 2 diabetes mellitus with the selected demographic variables among patient with chronic liver disease. The literature review was done and organised under various aspects on studies related to prevalence of type 2DM among patients with CLD. The research approach used for the study was quantitative approach and the design was non- experimental retrospective design, 50 samples were participated in the study by using convenient sampling technique. Demographic variables are assessed by using the statistical measurement and prevalence of type 2DM among patient with chronic liver disease. The level significance selected was p<0.05 level. The collected data was tabulated and analysed by using inferential statistics. The study showed that there is significant association between type 2DM with selected demographic variable.